To Raise Awareness of Higher Education Students about the Development of Vocal Pedagogy through the Science of Vocals and Modern Music - Boychayeva Nazbuvi Avazovna (International Journal on Integrated Education, 2022)
In ancient times, singing had a folk and religious character and did not require didactic training. Accompanied by musical instruments, they sang "natural", spontaneous simple melodies or choral prayers in the synagogues. The first documentary note on the existence of vocal art as a separate genre in music appeared when the song entered the church. The priests got a lot of inspiration from the folk repertoire. Due to the strong influence of the church at that time, the song was constantly evolving, forming a distinctive form of religious and secular elements. The topic is the development of vocal pedagogy through the study of vocal and modern music.